Adjuvant Radiotherapy Use by US Radiation Oncologists After Radical Cystectomy for Muscle-invasive Bladder Cancer. Issue 7 (July 2017) - Solanki, A.A.; Martin, B.; Korpics, M.; Small, C.; Harkenrider, M.M.; Mitin, T.
Abstract: Aims: Historic trials suggested significant toxicity with adjuvant radiotherapy (ART) after radical cystectomy for muscle-invasive bladder cancer (MIBC). However, recent trials have found improved locoregional control and the 2016 National Comprehensive Cancer Network (NCCN) guidelines recommend ART consideration for select patients at high risk of local recurrence. ART practice patterns among US radiation oncologists are unknown and we carried out a survey to explore current trends. Materials and methods: We conducted a survey of US radiation oncologists regarding the management of patients with cT2-3N0M0 transitional cell MIBC. Responses were reported using descriptive statistics. Chi-square and univariate logistic regression of clinical and demographic covariates were conducted, followed by multivariable logistic regression analysis to identify factors predicting for ART use. Results: In total, 277 radiation oncologists completed our survey. Nearly half (46%) have used ART for MIBC at least once in the past. In ART users, indications for ART include gross residual disease (93%), positive margins (92%), pathological nodal involvement (64%), pT3 or T4 disease (46%), lymphovascular invasion (16%) and high-grade disease (13%). On univariate logistic regression, ART use was associated with the number of years in practice ( P  = 0.04), pre-cystectomy radiation oncology consultation ( P  = 0.004), primarily treating MIBC patients fit for cystectomy ( P  = 0.01) and intensity-modulated radiotherapy use ( P  = 0.01). On multivariable logistic regression analysis, routine pre-cystectomy radiation oncology consultation (odds ratio 1.91, 95% confidence interval 1.04–3.51; P  = 0.04) and intensity-modulated radiotherapy use (odds ratio 2.77, 95% confidence interval 1.48–5.22; P  = 0.002) remained associated with ART use. Conclusions: ART use is controversial in bladder cancer, yet unexpectedly has commonly been used among US radiation oncologists treating patients with MIBC after radical cystectomy. NRG-GU001 was a randomised trial in the US randomizing patients with high-risk pathological findings for observation or ART after cystectomy. However, due to poor accrual it recently closed and thus it will be up to other international trials to clarify the role of ART and identify patients benefiting form this adjuvant therapy. Highlights: An electronic survey of US radiation oncologists was carried out. The goal was to investigate adjuvant radiotherapy (ART) use in bladder cancer. 46% of radiation oncologists had used ART at least once in the past after radical cystectomy. Respondents stated multiple indications prompted ART use. Multiple international trials are testing the benefit of ART in bladder cancer.